Strengthening research of turnover decreasing: bibliometric review - Tobing, Dahlia Lumban; Amir, Ja’far; ahmadi, Slamet (International Journal of Applied Finance and Business Studies, 2024)
A Bibliometric method could facilitate a comprehensive and subjective evaluation of current findings of research. Comparing theoretical and evidence, such as employee turnover phenomenon. Turnover is costly; therefore, Human Resources managers should avoid it. At least reduce turnover intention. From this paper finding, by leveraging bibliometric of Scopus metadata it reveals and recommended to closely make a commitment to fulfill employee rights (organizational commitment). It will encourage employees to get their job satisfaction and impacted to increase intention to stay in organization. Transformational leadership moderate relation employee turnover intention and organizational embeddedness. HR management should consider well when leveraging AI (Artificial Intelligent). Keep consistent due Organizational Commitment, aware to mental health and efficacy of employee. To ensure that, HR manager can do research using those variables to entire employee, staff and non-staff